Deep-level diversity and workgroup creativity: the role of creativity climate. Issue 4 (20th May 2020) - Tripathi, Nachiketa; Ghosh, Vinit
Abstract : Purpose: This paper aims to explore the effect of perceived "self-to-team" deep-level diversity on team's creative output from a social identity lens' view. Design/methodology/approach: An experimental study was designed ( n = 30 in each experimental condition, namely, homogeneous, heterogeneous and mixed) and vignettes were used to manipulate the experimental conditions. Employees from four Indian organizations participated in the experimental study. Findings: Results indicated that deep-level homogeneous group perceived higher team creative output as compared to the deep-level heterogeneous group. Perceived team creativity climate was found to mediate the effect of team diversity on team's creative output. Further, it was observed that the quality of perceived creativity climate (positive and negative) moderated the relationship between diversity and team's creative output. Practical implications: The diversity–climate–creativity model presented in the paper may help managers to understand how "deep-level" group composition affects a group's creative performance. The findings of this study may act as a platform for building effective diversity management policies. Originality/value: The current research has contributed to the limited team diversity and creativity literature. Based on the experimental study, the paper has uniquely investigated team diversity and creativity link along with examining the role of a mediator (creativity climate) and moderator (quality climate) in the relationship. As the study was conducted in Indian settings, the findings were interpreted based on the typical Indian psycho-social characteristics.